INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI METODE PEMBIASAAN PADA ANAK USIA DINI DI RA TAAM ADINDA KEPATIHAN MENGANTI GRESIK - Syaikhon, Muhammad; Saleh , Nanang Rokhman (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
RA TAAM Adinda is one of the early childhood education institutions that prioritize Islamic Religious Education. Many students memorize the Al-Quran and selected hadiths. This research is a type of field research with a qualitative descriptive approach. This study aims to determine the process of internalizing the values of Islamic religious education through habituation methods in early childhood at RA TAAM Adinda and to determine the supporting and inhibiting factors. Data collection techniques used observation, in-depth interviews, and documentation. Data analysis used data reduction, data presentation, and verification. The findings of this study can be concluded that the internalization of the values of Islamic Religious Education through habituation in early childhood at RA TAAM Adinda includes planning, implementation, and evaluation. This internalization activity begins when children arrive at school by getting used to saying greetings and shaking hands with teachers, reading prayers before entering class, performing Duha prayers in congregation, reading asmaul husna, and reading short letters and choice hadiths. The supporting factors are the existence of character education content in the school curriculum, motivation from schools for quality output that is noble, as well as adequate facilities and infrastructure. While the inhibiting factors are the different characteristics of children, environmental factors of students, funding that is still fully charged to the school, students are easily distracted, and monitoring from the curriculum center is minimal.